2021
DOI: 10.3389/fnut.2021.762277
|View full text |Cite
|
Sign up to set email alerts
|

As a Staple Food Substitute, Oat and Buckwheat Compound Has Health-Promoting Effects for Diabetic Rats

Abstract: Dietary intervention is crucial for the prevention and control of diabetes. China has the largest diabetic population in the world, yet no one dietary strategy matches the eating habits of the Chinese people. To explore an effective and acceptable dietary pattern, this study uses oat and buckwheat compound (OBC) as a staple food substitute and explored its effects on diabetic Sprague–Dawley rats. The model of diabetic rats was established by combining high-calorie feed and streptozotocin (STZ) injection. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A recent systematic review has indicated that higher quality carbohydrate intake during pregnancy can control blood glucose levels in GDM patients ( 31 ). An intervention experiment has indicated that oat and buckwheat compounds decrease the fasting glucose levels in diabetic rats ( 32 ). A clinical trial has reported that carbohydrate counting and adherence to the DASH diet decreases fasting blood glucose levels in GDM with metformin therapy ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review has indicated that higher quality carbohydrate intake during pregnancy can control blood glucose levels in GDM patients ( 31 ). An intervention experiment has indicated that oat and buckwheat compounds decrease the fasting glucose levels in diabetic rats ( 32 ). A clinical trial has reported that carbohydrate counting and adherence to the DASH diet decreases fasting blood glucose levels in GDM with metformin therapy ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, an increase in T. Protein and albumin levels, concomitant with decreases in urea and BUN levels, were highly significant after administering HFOE2 compared to all other groups. In a previous study [ 66 ], kidney function parameters were recovered to a normal state after the intervention of oats [ 68 ]. Oat extract was related to a reduction in the liver’s glucose production and increased insulin secretion, which is associated with improved kidney functions [ 64 , 67 ].…”
Section: Discussionmentioning
confidence: 99%